Do Funding Decisions, Dividend Policy, and Investment Decisions effect on Islamic Firm's Value? - Narita Ningrum, Mayangsari; Zulfanti, Lies (SAN Scientific, 2024)
This research aims to examine the influence of Funding Decisions, Dividend Policy and Investment Decisions on Company Value in Companies listed on the Jakarta Islamic Index (JII) for the 2017-2020 period. This research uses quantitative research with a descriptive research strategy. The population of this research is 30 companies listed on the JII for the 2017-2020 period. The sample selection in this study used purposive sampling with a total sample of 22 companies, so the number of observations was 88. The data used is secondary data. Data collection techniques through the company's official website. The research results prove that Funding Decisions have a significant positive effect on Company Value, Dividend Policy has a significant and negative effect on Company Value, and Investment Decisions have a significant and positive effect on Company Value. The managerial implication in this research is that the capital structure chosen can influence the company's cost of capital. Dividend decisions can also affect a company's share price. It is important to conduct careful analysis and consider the various factors that influence these decisions to ensure that the company operates efficiently and can increase value for shareholders